2020
DOI: 10.3390/ijerph17186538
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Hypertension Medications and Lifestyle Recommendations among Underserved African American Middle-Aged and Older Adults

Abstract: Background: For African American middle-aged and older adults with hypertension, poor adherence to medication and lifestyle recommendations is a source of disparity in hypertension outcomes including higher rates of stroke in this population relative to whites. Aims: To study demographic, social, behavioral, cognitive, and medical predictors of adherence to medication and lifestyle recommendations among underserved African American middle-aged and older adults with hypertension. Methods: This was a community-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 67 publications
3
24
0
Order By: Relevance
“…In various settings, improved medicine accessibility through FCPEM programs proved to help reduce patients' direct medical costs and possibly lead to increased patient participation, continuity of treatment, and better health outcomes [15,[24][25][26][27]. Furthermore, we found that patients with characteristics indicative of free medicine use in our study coincided with patients who had chronic illnesses and poor medicine use and adherence in previous studies [28][29][30]. This implies that FCPEM implementation can promote equitable access to medicines and improve the health outcomes of vulnerable populations.…”
Section: Discussionsupporting
confidence: 67%
“…In various settings, improved medicine accessibility through FCPEM programs proved to help reduce patients' direct medical costs and possibly lead to increased patient participation, continuity of treatment, and better health outcomes [15,[24][25][26][27]. Furthermore, we found that patients with characteristics indicative of free medicine use in our study coincided with patients who had chronic illnesses and poor medicine use and adherence in previous studies [28][29][30]. This implies that FCPEM implementation can promote equitable access to medicines and improve the health outcomes of vulnerable populations.…”
Section: Discussionsupporting
confidence: 67%
“…As previously reported, men have higher mortality rates than women in many non-sex-specific chronic conditions ( 26 , 27 ). This disparity may attribute to men's reduced health care utilization ( 28 , 29 ), poorer medication adherence ( 30 ), poorer dietary habits ( 31 ), higher rate of smoking ( 32 ), and higher alcohol consumption ( 33 ) when compared with women's. Regarding ethnicity, the Black–White divergence in the incidence of NCDs ( 34 ) and comorbid hypertension ( 35 , 36 ) can partly explain the corresponding disparity in mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Older age was associated with a higher level of adherence to recommended lifestyle modifications. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%